Recovery effect of transplantation of neural stem cells derived from bone marrow stromal cells on learning and memory dysfunction induced by temporal lobe epilepsy in rats - SHEN Wei-gao; LIU Yan-bo; LI Shu-bo; HE Xin (浙江大学学报. 农业与生命科学版)
In order to research the recovery effect of neural stem cells (NSCs) derived from bone marrow stromal cells (BMSCs) to transplant into hippocampus of rats with epilepsy induced by kanic acid on their learning and memory dysfunction and approach the theory about NSCs transplantation treating epilepsy, the BMSCs were segregated, cultured and differentiated into NSCs in vitro at first, and secondly the rat models of epilepsy were established with kanic acid. At last, the NSCs derived from BMSCs were transplanted into hippocampus of rats with epilepsy and the learning and memory ability of rats were tested with Morris maze. The expression levels of NSE, c-fos and SEZ-6 genes were detected by RT-PCR and at the same time, the protein levels of NSE, C-FOS and SEZ-6 were measured by Western blot. The results display that the BMSCs were successfully induced into NSCs in vitro. The impairment of learning and memory of epileptic rats was significantly improved after the NSCs were transplanted into their hippocampus. The mRNAs expression levels of NSE, c-fos, SEZ-6 and their proteins levels were down-regulated in hippocampus tissue, difference being obvious in transplantation group compared with positive control group and sham-graft group (P<0.05). It was indicated that the dysfunction of learning and memory of rats with epilepsy was markedly improved after transplantation of NSCs derived from BMSCs into hippocampus, and the mechanism might be correlated with NSE, c-fos and SEZ-6 expression down-regulation.